107-2x=25x+23

Simple and best practice solution for 107-2x=25x+23 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 107-2x=25x+23 equation:


Simplifying
107 + -2x = 25x + 23

Reorder the terms:
107 + -2x = 23 + 25x

Solving
107 + -2x = 23 + 25x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-25x' to each side of the equation.
107 + -2x + -25x = 23 + 25x + -25x

Combine like terms: -2x + -25x = -27x
107 + -27x = 23 + 25x + -25x

Combine like terms: 25x + -25x = 0
107 + -27x = 23 + 0
107 + -27x = 23

Add '-107' to each side of the equation.
107 + -107 + -27x = 23 + -107

Combine like terms: 107 + -107 = 0
0 + -27x = 23 + -107
-27x = 23 + -107

Combine like terms: 23 + -107 = -84
-27x = -84

Divide each side by '-27'.
x = 3.111111111

Simplifying
x = 3.111111111

See similar equations:

| 3x-2=3(x-0.6666666666666666) | | x^4+12x^2-27=0 | | 63y-42=64y | | 7x-1+22(x-1)=180 | | 6(x-4)+9=2x+4(-3+x) | | 3x^3-8x^2+4x=0 | | 5x+3y+12x-7xy= | | 16=1d+6 | | 4x+8+2x=5x-1 | | -4x^2-6x+4=0 | | 5x+3+6x-1=90 | | 4p-3q+7p-2q= | | -6(3-3)-8(6x+5)=32 | | 20x-27x-8=0 | | 3(cq-5)=2(q+5) | | 2x+5x+42=0 | | 9x+9=7x+39 | | 5x*12=126,000 | | -12x-35x-18=0 | | -61+2x=-5x+16 | | 55+0.5x=50 | | -61+2x=-5x | | -4+3x=2x+7 | | -8-x=4-2x | | -47-x=31+5x | | 3.7=0.5-y | | -4x+26=-28+2x | | -5x-15=25-x | | 7/9+5/14= | | 22+16x=166 | | 8-4(-7x+8)=11 | | -0.01x^2+0.4x-20=0 |

Equations solver categories